Efektivitas Penggunaan Multimedia Berbasis Web sebagai Tolak Ukur dalam Peningkatan Aspek Kognitif Taruna Calon Perwira Kapal - Vega F. Andromeda; Iing Mustain; Yeyen Herlina (SAINTARA, 2022)
A Web-based learning has been developed to facilitate the cadets of ship officers in preparing for onboard practice. The learning thematic material for marine practice preparation is carried out using a web-based learning of multimedia on the stemparala.or.id. The purpose of this study was to determine the achievement of the cadets' cognitive aspects, the improvement of the cadets' cognitive aspects, and the effectiveness of web-based multimedia learning on the stemprala.or.id. The study used teh quantitive approach and a quasi-experimental method with a Randomized sample Pretest-Posttest Design research design with 41 cadets from 120 cadets who were ready to work-practice on the sea. Quantitative data obtained from pretest and postest of cadet, The sampling technique in this study was random sampling technique. The results of the study showed that the achievement of cadet knowledge in the cognitive aspect was increased with a significant difference between pretest and posttest achievements. The achievement of the cadets' cognitive aspect, the average posttest cadets' cognitive achievement was significantly greater than the average cadets' pretest achievement. Improving the cognitive aspects of cadets on the use of web-based multimedia on the stemprala.or.id for the cognitive aspects of cadets obtained a score of 0.11 or (11%) in the low category. The effectiveness based on Cohen's test is 0.22, in the small category. These results provide an overview of the need to provide techniques for using thematic multimedia that are more interactive and provide more meaningful and authentic learning.